How does Levine's conservation model address the specific needs of postpartum women in relation to physical activity? : systematic review - Afnani Toyibah; Fitriana Kurniasari Solikhah; Rudi Hamarno; Ngesti w Utami; Reem Iafi AlMutairi; Ronal Surya Aditya (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction. Levine's Conservation Model is a theory that focuses on energy conservation, structural integrity, personal and social integrity, and a holistic approach to care. This study aims to provide a framework for healthcare providers to support postpartum women in maintaining their health and well-being through physical activity. Methods. A systematic review was conducted using the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. The data sources for this systematic review will include a comprehensive search of electronic databases such as PubMed, Scopus, and CINAHL, covering literature from their inception to the present date. Results. The PICO framework was used to define eligibility criteria for the systematic review. The results of the study indicate that the Levine Conservation Model effectively addresses the multifaceted needs of post-childbirth women by emphasizing energy conservation and structural integrity. The model's focus on structural integrity aids in the healing process and physical recovery after childbirth, addressing the unique physical challenges faced by post-natal women. Conclusion: The findings from the research highlight the significant benefits of using an integrative approach in post-partum care as encapsulated by the model.